INCREASING THE FRACTURE TOUGHNESS OF EROSION-RESISTANT LAYERED MATERIALS PRODUCED BY EXPLOSION WELDING - V. N. Kovalevski; Yu. G. Alekseev; E. V. Sagarda; I. V. Fomohina (Литьë и металлургия)
It is proposed to use the J-integral criterion that takes into account the plastic deformation at the crack tip for layered materials based on high-strength steel 38HN3MFA alloys and erosion resistant cobalt alloy ЭП 131, molybdenum alloy MT, which are destroyed according to the laws of elastic-plastic mechanics. The experimental technique for determining and numerical calculation of energetic J-integral has been described. Numerical modeling of the destruction process has shown good convergence with experimental researches. There was shown that the high-velocity deformation at explosive processing of steel forms structure with high parameters of strain crack toughness and significant increase of yield strength of a material.